Mal Pelayanan Publik Sebagai Praktik Inovasi Pemerintah Daerah Di Wilayah Provinsi Jawa Barat - Nur, Mohamad Ichsana (Program Studi Administrasi Negara Universitas Serang Raya, 2023)
Public sector innovation is currently a big political and administrative agenda and is stealing attention from developed democratic countries, and following it to a number of other developing countries. In the context of Indonesia as a developing country, the Government is committed to continuing to support public service innovation through a series of existing rules and regulations. West Java is included in the top five highly innovative provincial government versions of the Ministry of Home Affairs of the Republic of Indonesia. Of the 27 regencies/cities in West Java, it seems that Bekasi City is the only region that has succeeded in developing its government innovations in a good and superior manner. It was recorded that from 2018 to 2021, the Regional Government of Bekasi City through the Investment Service and One-Stop Integrated Services received an award as a public service provider in the